Trust, privacy, service quality, and brand image on the success of electronic customer relationship management - Muhammad Habil; Yunita Engriani (Universitas Negeri Padang, 2023)
The purpose of this study was to analyze the effect of trust, privacy, service quality, and brand image on the success of E-CRM Lazada customers in the city of Padang with customer satisfaction as a mediating variable. The population in this study are Lazada application users in the city of Padang and have made transactions at Lazada in the last 6 months. The sampling technique used was purposive sampling. The number of samples in this study was 210 people. Data collection uses a questionnaire and is processed with SEM PLS4. The results of this study indicate that: (1) there is a significant influence between trust and E-CRM. (2) there is a significant influence between privacy and E-CRM. (3) there is a significant relationship between service quality and E-CRM. (4) there is a significant influence between Brand Image and E-CRM. (5) there is a significant relationship between trust and customer satisfaction. (6) there is a significant influence between privacy and customer satisfaction. (7) there is a significant influence between service quality and customer satisfaction. (8) there is a significant influence between brand image and customer satisfaction. (9) there is a significant influence between customer satisfaction and E-CRM. (10) There is a significant relationship between trust in E-CRM through customer satisfaction. (11) There is a significant influence between privacy on E-CRM through customer satisfaction. (12) There is a significant influence between service quality on E-CRM through customer satisfaction. (13) There is a significant influence between brand image on E-CRM through customer satisfaction.